Urban morphology and crime patterns in urban areas: A review of the literature / Idris Isah Iliyasu, Aldrin Abdullah and Massoomeh Hedayati Marzbali - Iliyasu, Idris Isah; Abdullah, Aldrin; Marzbali, Massoomeh Hedayati (Universiti Teknologi MARA, Perak, 2022)
The emerging research on urban morphology provide sufficient explorations that result in a better understanding of crime areas and fear of crime in cities. Despite the effort so far, the existing literature on morphology of crime areas and pattern of crime presents different perspectives to the study of crime and spaces, reflecting the varied field of urban morphological research. There is a need to understand these perspectives in view of their directions and inherent limitations for effective understanding of crime pattern and urban morphogenesis in cities. The focus of the paper is on the understanding of different perspectives in the study of crime pattern and urban morphology in setting up an effective mechanism for crime prevention and control. Twenty (20) paper articles and six (6) theses published between 2010 - 2021 were selected based on the Environmental criminological research perspectives from the field of Geography, Urban Planning, Urban Design, Landscape Architecture and Architecture; and systematically reviewed based on their characteristics and then classified according to their relevance to environmental criminology for analysis and drawing of inferences. The findings indicated that, there is inadequate empirical research on the influence of urban morphology on crime pattern in cities. Therefore, the paper recommends for further research to focus on exploring the various links between elements of urban morphology and spatial distribution of crime in areas, and the explanations that could provide for effective crime prevention and control in cities.